PENGARUH CAHAYA TERHADAP AKTIVITAS METABOLISME IKAN LELE DUMBO (CLARIAS GARIEPINUS) PADA SIMULASI TRANSPORTASI SISTEM TERTUTUP - Ruddy Suwandi; Agoes Mardiono Jacoeb; Vickar Muhammad (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
Consumer demand for commodities is growing, especially for the type of fish that have high economis value, one of which is dumbo catfish (Clarias gariepinus). Handling of the transport system is needed to keep fish alive until the destination. The purpose of this research was to study the effect of light intensity on simulated fish either at rest or moving. The study was conducted with simulation of a closed system transportation for six hours and measuring the water quality each hour. The treatment used were a light simulation, dark simulation, non-simulated light, and dark non-simulation. DO values decrese from 5,0175 ppm to 2,3812 ppm after 6 hours transportation. Water temperature during research at 27,8-29,4˚C. PH values in the study range from 7,2 to 6,3 ppm. The values of carbondioxide increased during transportation. The highest concentration of ammonia presented after six hours in all treatment.The best treatment of this study was non-simulated light.Keywords : Catfish (Clarias gariepinus), closed system transport, water quality